Technocrats of the Imagination Art, Technology, and the Military-Industrial Avant-Garde - Beck, John (Duke University Press, 2020)
Technocrats of the Imagination traces the rise of collaborative art and technology labs in the U.S. from WWII to the present. Ryan Bishop and John Beck reveal the intertwined histories of the avant-garde art movement and the military-industrial complex, showing how radical pedagogical practices traveled from Germany's Bauhaus movement to the U.S. art world and interacted with government-funded military research and development in university laboratories. During the 1960s both media labs and studio labs leaned heavily on methods of interdisciplinary collaboration and the power of American modernity to model new modes of social organization. In light of revived interest in Black Mountain College and other 1960s art and technology labs, this book draws important connections between the contemporary art world and the militarized lab model of research that has dominated the sciences since the 1950s.